Management Strategy of the School’s Principal in Improving the Quality of Education at SMA Negeri 1 Tanjung Lubuk - Idrus, Roosmaria; Ahmad, Syarwani; Kesumawati, Nila (Yayasan Sembilan Pemuda Indonesia, 2023)
This research aims to describe and find out the Principal’s Strategic Management in Improving the Quality of Education at SMAN 1 Tanjung Lubuk. Data collection tools using interviews, documentation, observation, and literature review. Data analysis used descriptive qualitative analysis with research stages referring to Milles and Huberman’s theory, namely data collection, data reduction, data presentation, and concluding. The results of the study stated that strategic management to improve the quality of education at SMA Negeri 1 Tanjung Lubuk was carried out by establishing a program to improve the quality of learning. The principal sets the standards for graduates to be achieved. For these graduate standards to be achieved, the principal organizes learning activities according to achievement targets. In addition, the principal also emphasizes that the learning evaluation process carried out by the teacher is carried out objectively and sustainably.